PERAN PROGRAM KAMPUS MENGAJAR DALAM MENINGKATKAN KEMAMPUAN LITERASI DAN NUMERASI PESERTA DIDIK DI SDN 9 BARU - BARU TANGA KABUPATEN PANGKEP - Haerunnisa Haerunnisa; Bakhtiar Bakhtiar; Imam Suyitno (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2025)
This study aims to find out (1) an overview of the campus teaching program at 9 Baru Baru Tanga Public Elementary School, Pangkep Regency. (2) the teaching campus program in improving the literacy and numeracy of students at the 9 Baru Baru Tanga Elementary School, Pangkep Regency. (3) What factors support and hinder the implementation of the role of the teaching campus program in increasing the literacy and numeracy of students at 9 Baru Baru Tanga Public Elementary School, Pangkep Regency. This research approach is qualitative using a type of phenomenological research. To be able to achieve the research objectives, the researcher uses data collection techniques in the form of observation, documentation and interviews using research instruments in the form of interview guides, documentation forms (filling sheets). Using triangulation and member checks as procedures to check the validity of the data. Using data reduction, data models and drawing conclusions as data analysis techniques. The results of this study indicate that (1) the teaching campus program includes 4 roles, namely increasing literacy, increasing numeracy, assisting technology adaptation and improving school administration. (2) the role of the campus teaching program in increasing the literacy and numeracy of students in the New Tanga State Elementary School 9 Baru Tanga Pangkep Regency is mostly done by teaching in class using modified lesson plans, using appropriate strategies according to the age of the students so that the class is more fun while additional strategies in accordance with the field of study programs/students teaching campus programs as well as additional roles such as assisting technology adaptation and improving school administration. (3) the supporting factors are massive coordination between teachers, students and field supervisor, adequate infrastructure and teaching staff and what hinders are students playing too much, being lazy, teachers not mastering the use of laptops or computers and the lack of the latest reading books.